Utilization of mixed cellulolytic microbes from termite extract, elephant faecal solution and buffalo ruminal fluid to increase in vitro digestibility of King Grass - Prabowo, Agung; Padmowijoto, Soemitro; Bachruddin, Zaenal; Syukur, Abdul (Indonesian Animal Sciences Society, 2007)
Cellulose is a compound of plant cell walls which is difficult to be degraded because it composed of glucose monomers linked by Î²-(1.4)-bound. It will be hydrolysed by cellulase enzyme secreted by cellulolytic microbes. The effective digestion of cellulose needs high activity of cellulase enzyme. This research aims to increase in vitro king grass digestibility utilizing mixed cellulolytic microbes of termite extract, elephant faecal solution, and buffalo ruminal fluid. Twelve syringes contained gas test media were randomly divided into four treatments based on sources of microbe (SM), namely: S (SM: cattle ruminal fluid [S]), RGK (SM: mixed cellulolytic microbes of termite extract, elephant faecal solution, and buffalo ruminal fluid [RGK], with composition 1 : 1 : 1), S-RGK (SM: S + RGK, with composition 1:1), and TM (without given treatment microbe). Digestibility was measured using gas test method. Average of gas production treatment of S-RGK (70.2 + 0.6 ml) was higher and significantly different (P<0.01) compared to treatment of S (60.3 + 0.8 ml), RGK (40.8 + 2.3 ml), and TM (13.3 + 2.0 ml). Utilization of mixed cellulolytic microbes of termite extract, elephant faecal solution, and buffalo ruminal fluid (RGK) that combined with microbes of cattle ruminal fluid (S) could increase in vitro digestibility of king grass. Key Words: Cellulolytic Microbe, Termite Extract, Elephant Faecal, Buffalo Ruminal Fluid